Changing Mindset and Using of Language Game on Nawal Sa'dawi’s Al-Mar'ah wa al-Jins: A Perspective of Ludwig Wittgenstein - Arina Haque; Habil Abyad; Iffat Maimunah; Suo Yan Mei (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2022)
Each language has its own rules and pattern and a certain tendency. Language games are the rules of language for a particular purpose. Nawal Sa'dawi uses denotative meaning as criticism and disagreement about existing social phenomena. Therefore, this study aims to determine the form of language games in the book "al-Mar'ah wa al-Jins" by Nawal Sa'dawi based on the perspective of Ludwig Wittgenstein. This study uses an interpretation method to express linguistic diction in books and their meanings as human expressions. This study uses Wittgenstein's hermeneutic approach to reveal linguistic facts from the book's narrative. The source of this research data is taken from the book "Al-Mar'ah wa al-Jins" by Nawal Sa'dawi. Data collection techniques in this study used reading techniques and note-taking techniques. The analysis of this research uses the technique of analyzing the philosophy of language from Ludwig's perspective. The results of this study indicate that there are four kinds of language games in the book "al-Mar'ah wa al-Jins" by Nawal Sa'dawi, namely: (1) emphasis; (2) feminist language; (3) sarcasm; and (4) subtle persuasion. This language game aims to reveal facts and as a form of assertiveness from its users upon request or support.